Clinical outcomes of patients hospitalized for COVID-19 and evidence-based on the pharmacological management reduce mortality in a region of the Colombian Caribbean - Mara García-Posada; Sandra Aruachan-Vesga; Danis Mestra; Katherine Humánez; Héctor Serrano-Coll; Heriberto Cabrales; Álvaro Faccini; Salim Mattar (Elsevier, 2021)
Introduction: Despite the high volume of infections, some clinical aspects of this disease are still unknown. There are currently no studies in Colombia that describe the disease's clinical and treatment aspects in detail. Objective: Describe the characteristics and clinical management of a group of admitted patients with SARS-CoV-2 infection in a private clinic in Montería, Córdoba-Colombia. Patients and methods: A descriptive observational study was carried out between May and August 2020 in 209 hospitalized patients with a confirmed diagnosis of COVID-19. Upon admittance, clinical, sociodemographic characteristics, comorbidities, and complications were analyzed. Additionally, the effect of the following medications was described: 1-antibiotics (cefepime, piperacillin, tazobactam, meropenem, vancomycin) + low molecular weight heparin (LMWH) + corticosteroids (dexamethasone-methylprednisolone) + colchicine. 2- Antibiotic + LMWH + corticosteroids. 3-LMWH + corticosteroids. 4-LMWH + corticosteroids + colchicine. 5-Other treatments (Tocilizumab). Results: 107 (51%) of the 209 patients with a confirmed diagnosis of COVID-19 passed away. The main comorbidities related to mortality of these hospitalized patients with COVID-19 were obesity and kidney disease (P < 0.05). The main complications associated with fatal outcomes in this group of patients were Acute Respiratory Distress Syndrome (ARDS) and sepsis (P < 0.05). Furthermore, it was evidenced that the colchicine combination showed a significant difference in reducing mortality in hospitalized patients compared to the other therapeutic regimens (P < 0.05). Conclusion: A mortality rate of 51% was found attributable to several factors such as advanced age, obesity, kidney disease, and an average time in days of late consultation. The implementation of the colchicine combination could reduce the mortality rate in this disease.